2021
DOI: 10.1039/d1fo00311a
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Laminaria japonica: an insight into the current research on structural features and biological properties

Abstract: Laminaria japonica, one of the most widespread seafood consumed in China and many other nations, has been traditionally utilized as an effective therapeutically active substance for treating the weight loss,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 111 publications
1
20
0
Order By: Relevance
“…For example, the fucoidan fraction of S. japonica showed the optimal anti-inflammatory activity in concentrations of 50-200 μg/mL [49] and 50-400 μg/mL [50], respectively. Besides, some studies reviewed the biological activities of fucoidan, and considered that the content of fucose, sulfate groups, molecular weight, and position of the glycosidic linkage would affect the biological activities of fucoidan [32,52,53]. Ye et al (2020) indicated that the purified fucoidan, from 50 to 200 μg/mL (246.4 KDa), with high sulfate group (36.94%) and rich in fucose (24.15%), had better anti-inflammatory activity [49].…”
Section: Cell Viability and No Production To Ljnfmentioning
confidence: 99%
“…For example, the fucoidan fraction of S. japonica showed the optimal anti-inflammatory activity in concentrations of 50-200 μg/mL [49] and 50-400 μg/mL [50], respectively. Besides, some studies reviewed the biological activities of fucoidan, and considered that the content of fucose, sulfate groups, molecular weight, and position of the glycosidic linkage would affect the biological activities of fucoidan [32,52,53]. Ye et al (2020) indicated that the purified fucoidan, from 50 to 200 μg/mL (246.4 KDa), with high sulfate group (36.94%) and rich in fucose (24.15%), had better anti-inflammatory activity [49].…”
Section: Cell Viability and No Production To Ljnfmentioning
confidence: 99%
“…Additionally, the PSs extracted from LJ exhibit a variety of health-beneficial biofunctions, such as anti-oxidation ( 4 , 5 ), anti-inflammatory ( 6 , 7 ), lipid-lowering ( 8 , 9 ), anti-diabetes ( 10 ), and anti-obesity effects ( 11 ). Of note, the discrepant bioactivities of LJ-derived PS (LJPS) might occur owing to different isolation procedures or sources ( 7 , 12 , 13 ) and more likely due to the differentiated molecular structure of the LJPS.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the molecular structure of LJPS, most current research has focused on the analyses of monosaccharide composition, molecular weight, glycosidic linkages, and substituted groups via high-performance liquid chromatography (HPLC), near-infrared spectroscopy, gel penetration chromatography, and other methods. Moreover, with respect to the conventional indicators of molecular structure, recent studies have addressed the pivotal role of PS chain length (degree of polymerization, DP) and spatial conformation in their bioactivities ( 11 , 17 , 18 ). Similarly, many studies on inulin and fructan have shown that DP value is one of the most crucial factors affecting their biological functions ( 11 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sea tangle (Laminaria japonica Aresch), a type of edible brown algae, has long been widely consumed as a food supplement and medicinal use in East Asia including Korea. This seaweed is rich in various lipophilic components, hydrophilic fibers, and minerals, and various pharmacological effects were extensively reported in several previous studies [11][12][13][14]. Interestingly, fermented sea tangle extract (FST) with Lactobacillus brevis BJ20 content 5.56% of gamma-aminobutyric acid (GABA) that was 49.5% among total free amino acids [15].…”
Section: Introductionmentioning
confidence: 94%